Analysis of Cost and Time To Complete of Office Project with The Earned Value Method: (Case study: Office of Bahtera Elang Perak Indonesia Surabaya) - Linda Nailufar; Budi Witjaksana; Esti Wulandari (CV. Proaksara Global Transeduka, 2024)
The rescheduling of the initial schedule carried out on the Bahtera Elang Perak Indonesia Office Construction project has an impact on increasing the duration of work causing the project completion target to be delayed from the time it should be. Increasing the project completion target can affect the amount of costs incurred. The contract value for this office construction project is Rp. 13,908,226,157 with a work duration of 43 weeks to 54 weeks. The current condition of work progress at week 31 is -0.225% while the total actual cost or that has been incurred during the work is Rp. 3,191,740,254. To overcome this, an analysis is carried out on the value of the estimate at complete (EAC) and time estimate (TE) of the Surabaya BEPI Office Construction Project using the earned value method. This method combines the elements of cost, schedule, and work performance. The earned value method aims to determine the estimated cost and time of project completion. From the results of the analysis conducted in the 41st week, it was obtained that the estimated cost and time to complete the project implementation (EAC) was 14,289,833,105, - and the estimated time (TE) was 499 days, which was 121 days later than the original schedule.